PROCRASTINATION IN ACADEMIC LEARNING - E. Petrova (Вестник университета)
The paper considers the phenomenon of procrastination. The article gives a short review of this phenomenon and highlights its importance and relevance in the present context. Psychological analysis of procrastination includes its connection with mental health of an individual, his/her self-confidence, self-respect, stress, anxiety and fears. Both teachers and students are subject to procrastination. In this respect the emphasis is placed on the importance of creating comfortable psychological environment in study groups. The given material can be interesting for all participants of the learning process who face the problems of procrastination on a regular basis.